Maximum catalytic activity of Pt3M in Li-O-2 batteries: M = group V transition metals - Kang, Yong-Ju; Jung, Sung Chul; Kim, Hyung-Jin; Han, Young-Kyu; Oh, Si Hyoung (ELSEVIER SCIENCE BV, 2016)
Li-O-2 batteries are considered as promising power sources for electric vehicles due to their remarkably high energy density. However, low rate capability and short cycle life caused by sluggish oxygen reduction/evolution reaction (ORR/OER) kinetics limit their practical applications. Here, we investigate the catalytic activities of Pt3M bimetallic alloys (M = 3d, 4d, and 5d transition metals) for improving the ORR and OER kinetics using first-principles calculations. We found that the group 5 elements (V, Nb, and Ta in 3d, 4d, and 5d periods, respectively) are the most effective alloy components for high catalytic activity. Pt3V, Pt3Nb, and Pt3Ta alloys exhibit considerably lower ORR and OER overpotentials (by 71-77% and 57-59%, respectively) than those of Pt. The catalytic activities are successfully described by the adsorption strengths of reaction intermediate species (Li and LiO2) on the alloy surface rather than the d-band center of the alloy surface and are fundamentally controlled by the amount of surface charge. The superior catalytic activities of Pt3M alloys with the group 5 elements originate from their electron-rich surfaces and can also be interpreted in terms of the integration of mechanical interplay and chemical interplay of Pt and M, i.e., an appropriate trade-off between surface strain and ligand effects. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: OXYGEN REDUCTION REACTION; REDUCED GRAPHENE OXIDE; LI-AIR; COMPUTATIONAL DESIGN; POROUS GRAPHENE; RATE CAPABILITY; ELECTROCATALYSTS; MORPHOLOGY; STRAIN; NANOPARTICLES